Gastos e ingresos en la actividad caprina extensiva en México. - Rebollar-Rebollar, Samuel (2012)
The objective of this work was to determine production costs and profitability of goats in extensive production systems. The research was carried out during January-June 2011 in the localities Monte de Dios and San Lucas delMaíz, Tejupilco municipality, State of Mexico. The information came from a survey of 37 producers. Production costs considered money only actually paid by producers, there were items that were not included, since they were absorbedby the family economy, or were opportunity costs equal tozero, or omitted because they were not used in practice. The production cost per head was US$ 8.7; of this, variable and fixed costs were US$ 3.8 and US$ 4.9. The main variablecost was parasite control and tha main fixed cost was maintenace of stabullating installations. The average revenue from sales considered a weight of 35 kg and a price of two dollars per kilogram, bringing the total income to US$ 71.2 per animal. With this, the net profi t was US$ 62.5, while thebenefi t-cost ratio was 8.1. The cost of producing goats underthis system of production was less than a third of revenues from sales, due to the relatively low production costs, so that profi t per unit sold was seven times the cost of production.